2010
DOI: 10.1007/s11243-010-9360-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic epoxidation potential of oxodiperoxo molybdenum(VI) complexes with 2-hydroxybenzohydroxamate and 2-hydroxybenzoate: the crystal structure of PPh4[MoO(O2)2(HBA)]

Abstract: PPh 4 ) 2 [MoO(O 2 ) 2 (SHAH)]ÁH 2 O and PPh 4 [MoO-(O 2 ) 2 (HBA)] (SHAH 3 = 2-hydroxybenzohydroxamic acid and HBAH = 2-hydroxybenzoic acid) have been synthesized and characterized by physico-chemical and spectroscopic methods. In addition, the second complex has been structurally characterized by single-crystal X-ray diffraction analysis. We have compared the catalytic activities of these two new complexes, together with the previously reported PPh 4 [MoO(O 2 ) 2 (BZ)] (BZH = benzoic acid), with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The CV and DPV analysis indicated that variation of the cation structure does not significantly affect the electrochemical properties of the complex anion. This is the only catalytic study which follows the studies by Garah et al [31,32,34,60] for [Cat] m [MoO(O 2 ) 2 (L) n ] type complexes as epoxidation catalysts using TBHP as oxidant. The type of cation may influence the catalytic performance.…”
Section: Substratementioning
confidence: 89%
See 2 more Smart Citations
“…The CV and DPV analysis indicated that variation of the cation structure does not significantly affect the electrochemical properties of the complex anion. This is the only catalytic study which follows the studies by Garah et al [31,32,34,60] for [Cat] m [MoO(O 2 ) 2 (L) n ] type complexes as epoxidation catalysts using TBHP as oxidant. The type of cation may influence the catalytic performance.…”
Section: Substratementioning
confidence: 89%
“…Later, in 2005, Maiti et al [13] reported the anionic complex [PPh 4 ][MoO(O 2 ) 2 (QO)], with QOH = 8-quinolinol, as an active catalyst for the oxidation of alcohols, sulphides and amines using H 2 O 2 as oxidant. However, in the same decade, Garah et al [31,32,34,60] found that several monoanionic complexes of the type [Cat][MoO(O 2 ) 2 (L) n ] ([Cat] + = tetraorganophosphonium type cation, and L = conjugated base of 2-hydroxybenzoic acid, benzoic acid [31], pyridine-2-carboxylic acid [32], or an oxime such as (hydroxyphenyl)ethenone [60], salicylaldoxime [34] and pyridine-2-carboxaldoxime [32]) were inactive as catalysts for olefin epoxidation using H 2 O 2 as oxidant (co-additives were required for olefin epoxidation to occur).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation